Optimizing Ultrasonic Extraction of Antioxidants and Polyphenols in Five Indigenous Remedial Plants Using Box-Behnken Design Combined with Response Surface Methodology - Amrutanand, Tripathy; Alkanad, Maged; Shankar, Nischith Sirawase; Venkatappa, Annegowda Hardur (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim/Background: This study aimed to optimize the ultrasonic extraction of antioxidants and polyphenols from five indigenous medicinal plants Cassia auriculata, Celastrus paniculatus, Moringa concanensis, Murraya koenigii, and Alternanthera sessilis using Box-Behnken Design (BBD) and Response Surface Methodology (RSM). The goal was to enhance the extraction efficiency of these bioactive compounds, which are crucial for mitigating oxidative stress and preventing chronic diseases. Materials and Methods: The extraction process was optimized by varying key parameters: extraction time (45-60 min), solvent ratio (40-80% ethanol-water mixture), and solid-liquid ratio (1:5 to 1:15 g/mL), with plant source as a categorical factor. The response Variables measured were DPPH scavenging Activity (VCEAC) and Total Phenolic Content (TPC). The study employed BBD and RSM to develop a predictive model for these responses. Results: The results indicated that extraction duration, solvent concentration, and solid-liquid ratio significantly impacted antioxidant activity. Cassia auriculata exhibited the highest Antioxidant activity (VCEAC of 14.59 μg) under optimal conditions: 56.9 min extraction, 77.54% solvent concentration, and a 1:6.3 g/mL solid-liquid ratio. Celastrus paniculatus followed closely. The predictive model showed high accuracy with R² values of 0.9551 for antioxidant activity and 0.9415 for TPC. Conclusion: The study successfully optimized the ultrasonic extraction parameters for antioxidants and polyphenols from the selected medicinal plants. The findings underscore the importance of selecting appropriate plant sources based on desired medicinal properties and demonstrate the potential for utilizing these extracts in pharmaceuticals, supplements, and cosmetics. The combination of RSM and BBD proved effective in providing a reliable predictive model for extraction efficiency.
Keywords: Antioxidant; Box-Behnken Design; Optimization; Polyphenols; Ultra-sonication.